A Small Molecule Walks Along a Surface Between Porphyrin Fences That Are Assembled In Situ1. (29th April 2015) - Haq, Sam; Wit, Bareld; Sang, Hongqian; Floris, Andrea; Wang, Yu; Wang, Jianbo; Pérez‐García, Lluïsa; Kantorovitch, Lev; Amabilino, David B.; Raval, Rasmita
Abstract An on‐surface bimolecular system is described, comprising a simple divalent bis(imidazolyl) molecule that is shown to "walk" at room temperature via an inchworm mechanism along a specific pathway terminated at each end by oligomeric "fences" constructed on a monocrystalline copper surface. Scanning tunneling microscopy shows that the motion of the walker occurs along the [1<alternatives> <![CDATA[$\bar 1$]]> <inline-graphic xlink:href="ark:/27927/pgjqk1sgz8" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives>0] direction of the Cu surface with remarkably high selectivity and is effectively confined by the orthogonal construction of covalent porphyrin oligomers along the [001] surface direction, which serve as barriers. Density functional theory shows that the mobile molecule walks by attaching and detaching the nitrogen atoms in its imidazolyl "legs" to and from the protruding close‐packed rows of the metal surface and that it can transit between two energetically equivalent extended and contracted conformations by overcoming a small energy barrier.